Without the novel : romance and the history of prose fiction - Black, Scott, 1964- (University of Virginia Press, 2019)
No genre manifests the pleasure of reading--and its power to consume and enchant--more than romance. In suspending the category of the novel to rethink the way prose fiction works, Without the Novel demonstrates what literary history looks like from the perspective of such readerly excesses and adventures. Rejecting the assumption that novelistic realism is the most significant tendency in the history of prose fiction, Black asks three intertwined questions: What is fiction without the novel? What is literary history without the novel? What is reading without the novel? In answer, this study draws on the neglected genre of romance to reintegrate eighteenth-century British fiction with its classical and Continental counterparts. Black addresses works of prose fiction that self-consciously experiment with the formal structures and readerly affordances of romance: Heliodorus's Ethiopian Story, Cervantes's Don Quixote, Fielding's Tom Jones, Sterne's Tristram Shandy, and Burney's The Wanderer. Each text presents itself as a secondary, satiric adaptation of anachronistic and alien narratives, but in revising foreign stories each text also relays them. The recursive reading that these works portray and demand makes each a self-reflexive parable of romance itself. Ultimately, Without the Novel writes a wider, weirder history of fiction organized by the recurrences of romance and informed by the pleasures of reading that define the genre.